BEGONIA LECONGKIETII (SECT. PETERMANNIA), A NEW SPECIES FROM MOUNT DẦU, SOUTH CENTRAL COAST REGION, VIETNAM - Lý, N.-S.; Peng, C.-I.; Hughes, M. (Edinburgh Journal of Botany, 2018)
A new species of Begonia (B. lecongkietii N.S.Lý & M.Hughes) is described from Mount Dầu in the South Central Coast Region, Vietnam, an area with an abundance of recently described endemic plant taxa. The new species is allied to Begonia lamxayana Souvann., which occurs 600 km away in Laos, differing chiefly in having larger villose tepals with an undulate margin and larger androecium with 86–116 (versus 20–30) stamens. Begonia lecongkietii is considered Critically Endangered, owing to its small area of occupancy and decline of habitat quality.